Conductive paste

CN117597753BActive Publication Date: 2026-10-16MURATA MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280047085.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-07-16
Publication Date
2026-10-16
Estimated Expiration
2042-07-16

AI Technical Summary

Technical Problem

这成为使内部电极的覆盖率下降的原因

Benefits of technology

[0015] If the internal electrodes of a multilayer ceramic capacitor are formed using the conductive paste of the present invention, the coverage of the internal electrodes can be improved. Therefore, even if the internal electrodes are thinned, a high coverage of the internal electrodes can be maintained, enabling the multilayer ceramic capacitor to achieve a large capacitance without hindering its development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117597753B_ABST
    Figure CN117597753B_ABST
Patent Text Reader

Abstract

Provided is a conductive paste for internal electrodes that can maintain a relatively high coverage even if the internal electrodes of a multilayer ceramic capacitor are thinned. A conductive paste for forming internal electrodes (4, 5) of a multilayer ceramic capacitor (1) manufactured through a firing process, containing a conductive metal powder, a ceramic powder, an organic solvent, and an organic binder, at least a portion of the ceramic powder being a powder containing an ABO3-type oxide having a specific ionic radius, in which the A-site element in the ABO3-type oxide has an ionic radius in a 6-coordination state that is a ratio of 0.97 or more and 1.04 or less to an ionic radius in a 6-coordination state of a metal element contained in the conductive metal powder. Preferably, when the conductive metal powder contains nickel, the ABO3-type oxide having the specific ionic radius is at least one selected from the group consisting of NiTiO3, MgTiO3, and MnTiO3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to conductive pastes, and in particular, to conductive pastes for forming internal electrodes in multilayer ceramic capacitors. Background Technology

[0002] Typically, a multilayer ceramic capacitor includes a laminate and multiple external electrodes. The laminate has multiple stacked dielectric layers comprising ceramic and multiple internal electrodes disposed along multiple interfaces between the dielectric layers. The multiple external electrodes are disposed on the outer surface of the laminate and are electrically connected to the internal electrodes. The internal electrodes include multiple first internal electrodes and multiple second internal electrodes alternately arranged in the stacking direction of the laminate. The external electrodes include a first external electrode electrically connected to the first internal electrodes and a second external electrode electrically connected to the second internal electrodes.

[0003] To achieve miniaturization and high capacitance in this type of multilayer ceramic capacitor, it is necessary to thin the dielectric layer and internal electrodes, and improve the coverage of the internal electrodes (electrode continuity). Generally, in the firing process of manufacturing multilayer ceramic capacitors, the sintering temperature of the conductive metal particles contained in the conductive paste film that should form the internal electrodes is lower than the sintering temperature of the ceramic forming the dielectric layer. Therefore, the metal particles contained in the internal electrodes sinter first. This leads to a decrease in the coverage of the internal electrodes. In particular, for internal electrodes that are thinned to a thickness of less than 1 μm, the coverage tends to decrease. This decrease in coverage hinders the achievement of high capacitance.

[0004] Therefore, in order to form a thin internal electrode with high coverage, the sintering temperature of the conductive metal particles contained in the conductive paste film to be the internal electrode needs to be further increased during the firing process in the manufacture of multilayer ceramic capacitors. This allows the sintering temperature of the metal particles contained in the conductive paste film to be the internal electrode to be close to the sintering temperature of the ceramic constituting the dielectric layer, and enables closer synchronization of shrinkage timing between the internal electrode and the dielectric layer during sintering. As a result, the coverage of the internal electrode increases, enabling the realization of larger capacitance.

[0005] It is known that, in order to improve the coverage of the internal electrode and achieve a large capacitance using the methods described above, a ceramic material with a composition similar to that of the ceramic constituting the dielectric layer is added to the conductive paste used for forming the internal electrode, as described in paragraph 0004 of Patent Document 1 (Japanese Patent Application Publication No. 2016-31807), i.e., a common material. By adding the common material, the sintering time of the metal particles contained in the conductive paste film, which should become the internal electrode, can be shifted to a higher temperature side, and the sintering temperature of the metal particles contained in the conductive paste film can be made close to the sintering temperature of the ceramic constituting the dielectric layer.

[0006] Prior art literature

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2016-31807 Summary of the Invention

[0009] The problem the invention aims to solve

[0010] However, it is undeniable that even with the addition of common materials to the conductive paste used for forming the internal electrodes, the sintering temperature of the metal particles contained in the conductive paste is still lower than the sintering temperature of the ceramics constituting the dielectric layer, and further improvement is desired. In particular, regarding internal electrodes, for example, those that are thinned to a thickness of less than 1 μm, there is a strong demand for an effective solution to the problem of reduced coverage that hinders the achievement of large capacitance.

[0011] Therefore, the present invention was made in view of such problems, and its object is to provide a conductive paste for forming internal electrodes that can maintain a relatively high coverage even when the internal electrodes are thinned.

[0012] Technical solutions for solving the problem

[0013] The present invention relates to a conductive paste for forming internal electrodes of a multilayer ceramic capacitor, comprising conductive metal powder, ceramic powder, organic solvent, and organic binder. To solve the aforementioned technical problem, the present invention is characterized in that at least a portion of the ceramic powder is a powder comprising an ABO3-type oxide with a specific ionic radius, wherein the ratio of the ionic radius of the A-site element in the ABO3 oxide to the ionic radius of the metal element contained in the conductive metal powder under 6-coordinate conditions is 0.97 or more and 1.04 or less.

[0014] Invention Effects

[0015] If the internal electrodes of a multilayer ceramic capacitor are formed using the conductive paste of the present invention, the coverage of the internal electrodes can be improved. Therefore, even if the internal electrodes are thinned, a high coverage of the internal electrodes can be maintained, enabling the multilayer ceramic capacitor to achieve a large capacitance without hindering its development. Attached Figure Description

[0016] Figure 1 This is a schematic cross-sectional view of a multilayer ceramic capacitor 1 using the conductive paste of the present invention. Detailed Implementation

[0017] Reference Figure 1 The structure of the multilayer ceramic capacitor 1 using the conductive paste of the present invention will be described.

[0018] A multilayer ceramic capacitor 1 includes a multilayer body 2. The multilayer body 2 includes multiple stacked dielectric layers 3 comprising ceramic and multiple internal electrodes 4 and 5 arranged along the interfaces between the multiple dielectric layers 3. The internal electrodes 4 and 5 can be classified as multiple first internal electrodes 4 and multiple second internal electrodes 5 alternately arranged in the stacking direction of the multilayer body 2. More specifically, on the outer surface of the multilayer body 2, a first external electrode 6 and a second external electrode 7 are respectively provided on each opposing end face. The first external electrode 6 is electrically connected to the first internal electrode 4, and the second external electrode 7 is electrically connected to the second internal electrode 5.

[0019] The dielectric layer 3, for example, comprises a ceramic with ABO3 as the main component (A being at least one of Ba, Ca, and Sr, and B being at least one of Ti and Zr). Alternatively, the ceramic may use ABO3 as the main component and further include at least one of Mn, Mg, Si, Y, Dy, and Gd as secondary components.

[0020] The internal electrodes 4 and 5 preferably contain Ni as a conductive component. Furthermore, as a characteristic component, the internal electrodes 4 and 5 contain at least one selected from NiTiO3, MgTiO3, and MnTiO3. NiTiO3, MgTiO3, and MnTiO3 have an ilmenite crystal structure.

[0021] Furthermore, as can be seen from the experimental examples described later, in a preferred embodiment, the dielectric layer 3 comprises a ceramic with at least one selected from BaTiO3, SrTiO3 and CaZrO3 as the main component, and the internal electrodes 4 and 5 comprise nickel as a conductive component. As ceramic materials, they comprise at least one selected from NiTiO3, MgTiO3 and MnTiO3, and further comprise at least one selected from BaTiO3, SrTiO3 and CaZrO3 contained in the dielectric layer 3 as needed.

[0022] External electrodes 6 and 7 are formed, for example, by applying a conductive paste with Ag or Cu as the main conductive component to the end face of the laminate 2 and then sintering it. If necessary, Ni plating and Sn plating may also be performed on the thick film formed by sintering, for example.

[0023] A multilayer ceramic capacitor 1 is manufactured, for example, through the following steps. First, a ceramic slurry containing raw material powder of ceramic having the composition described above is prepared. Next, a ceramic green sheet is formed by applying a suitable sheet forming method to the ceramic slurry. Next, a conductive paste, which should become the internal electrodes 4 and 5, is applied to a given ceramic green sheet by printing or the like. Next, the multiple ceramic green sheets are stacked and then pressed together to obtain an untreated multilayer. Next, the untreated multilayer is fired. In this firing process, the ceramic green sheet becomes the dielectric layer 3. Then, external electrodes 6 and 7 are formed on the end faces of the multilayer 2.

[0024] Preferably, the conductive paste used in manufacturing the above-described multilayer ceramic capacitor 1, which should be the internal electrodes 4 and 5, is prepared as follows.

[0025] In the production of conductive paste, the following steps are performed: Step 1, preparing a ceramic powder slurry containing ceramic powder, organic solvent and dispersant; Step 2, preparing a metal powder slurry containing conductive metal powder, organic solvent and dispersant; Step 3, preparing an organic carrier containing organic resin components and organic solvent; and Step 4, mixing the above-mentioned ceramic powder slurry, metal powder slurry and organic carrier.

[0026] More specifically, in the first step, a ceramic powder slurry is prepared by mixing ceramic powder and a dispersant in an organic solvent.

[0027] As the aforementioned ceramic powder, for example, a ceramic powder containing at least one selected from NiTiO3, MgTiO3 and MnTiO3 as ABO3 oxides can be used. Furthermore, in addition, a ceramic powder containing at least one selected from BaTiO3, SrTiO3 and CaZrO3 as common materials is sometimes used.

[0028] When the conductive metal powder contained in the metal powder slurry produced by the second process described later contains nickel, the aforementioned NiTiO3, MgTiO3, and MnTiO3, which are ABO3 oxides, become ABO3-type oxides with specific ionic radii, wherein the ratio of the ionic radius of the element at the A site in ABO3 under 6-coordinate to the ionic radius of the nickel element under 6-coordinate is 0.97 or more and 1.04 or less.

[0029] According to the ceramic powder containing at least one selected from NiTiO3, MgTiO3, and MnTiO3 as ABO3 oxides, during sintering, possible reactions between the ceramic powder and the conductive metal powder contained in the metal powder slurry prepared in the second step can be suppressed. Alternatively, the ceramic powder may be mainly composed of the aforementioned ABO3 oxide, and further contain at least one of Mn, Mg, Si, Y, Dy, and Gd as secondary components. With such secondary components, grain growth of ceramic particles can be suppressed, and sometimes sintering of metal particles can be effectively suppressed.

[0030] As a dispersant mixed with ceramic powder in the first step, an anionic polymeric dispersant can be used, for example, and as an organic solvent, dihydroterpineol can be used, for example.

[0031] In the second step, a metal powder slurry is prepared by mixing conductive metal powder and a dispersant in an organic solvent. For example, a powder containing metallic nickel or its alloys can be used as the conductive metal powder. The same dispersant and organic solvent used in the second step can be used as those used in the first step.

[0032] In the third step, an organic carrier is produced by mixing an organic resin component with an organic solvent. For example, ethyl cellulose resin can be used as the organic resin component. Regarding the organic solvent used in the third step, the same organic solvent used in the first step can also be used.

[0033] In step 4, the aforementioned ceramic powder slurry, metal powder slurry, and organic carrier are mixed. This yields a conductive paste that should serve as internal electrodes 4 and 5. This conductive paste contains a ceramic powder slurry, which, as previously described, contains ceramic powder. This ceramic powder contains at least one selected from NiTiO3, MgTiO3, and MnTiO3, which are ABO3 oxides with specific ionic radii. Therefore, the internal electrodes 4 and 5 of the multilayer ceramic capacitor 1 manufactured through the sintering process contain at least one selected from NiTiO3, MgTiO3, and MnTiO3.

[0034] [Experimental Example]

[0035] Next, experimental examples performed to confirm the effects based on the present invention will be described.

[0036] In this experimental example, nickel powder was prepared as the conductive metal powder contained in the conductive paste for forming the internal electrode.

[0037] On the other hand, in addition to NiTiO3, MgTiO3, and MnTiO3, CuTiO3, BaTiO3, CaZrO3, and SrTiO3 were also prepared as ABO3 oxides with specific ionic radii constituting the ceramic powder contained in the conductive paste for forming the internal electrode. Table 1 shows the "crystal structure," "coordination number," "A-site element," and "ionic radius" for these ABO3 oxides. Furthermore, although Ba, Ca, and Sr are 12-coordinated in their original perovskite structure, they are also 6-coordinated when gradually dissolved at the sites of 6-coordinated elements (Ni, Mg, Mn) in the ilmenite structure; therefore, the "ionic radius" in Table 1 shows the values ​​under 6-coordinated conditions.

[0038] [Table 1]

[0039]

[0040] The following describes Experiment 1, Experiment 2, and Experiment 3, which involved changing the ceramic raw material constituting the dielectric layer.

[0041] (Experimental Example 1) The main component of the ceramic that constitutes the dielectric layer: BaTiO3

[0042] 1. Preparation of BaTiO3-based ceramic raw materials constituting the dielectric layer

[0043] As starting materials, powders of the main components BaCO3 and TiO2 were weighed and mixed in a ball mill for 72 hours, followed by heat treatment at a maximum temperature of 1000℃ for 2 hours to obtain heat-treated powder. On the other hand, as secondary components, powders of MnO, Dy2O3, MgO, SiO2, and BaCO3 were prepared and weighed, ensuring that the secondary component powders, relative to the heat-treated powder, had a composition ratio of 100BaTiO3 + 0.5Mn + 1.0Dy + 1.0Mg + 1.0Si + 2.0Ba. These secondary component powders were added to the heat-treated powder and mixed in a ball mill for 24 hours, followed by drying to obtain BaTiO3-based ceramic raw material powder.

[0044] 2. Preparation of conductive paste for internal electrode formation

[0045] The powder of “ABO3 oxide” shown in Table 2 below and the BaTiO3-based ceramic raw material powder used for the dielectric layer are used as the ceramic powder contained in the conductive paste for forming the internal electrode.

[0046] Weigh the powders of these "ABO3 oxides" and BaTiO3 ceramic raw materials to achieve the "addition ratio" shown in Table 2. Use a media-free stirred mill to premix these powders, dihydroterpineol as an organic solvent, and an anionic polymeric dispersant as a dispersant. Then, disperse the mixture using a media stirred mill to produce a ceramic powder slurry (step 1).

[0047] On the other hand, a metal powder slurry (step 2) was prepared by dispersing nickel powder (as a conductive metal powder), dihydroterpineol (as an organic solvent), and an anionic polymeric dispersant (as a dispersant) using a three-roll mill.

[0048] Then, ethyl cellulose resin, which is an organic resin component, and dihydroterpineol, which is an organic solvent, are mixed to obtain an organic carrier (step 3).

[0049] Then, the metal powder slurry and the ceramic powder slurry were added to the organic carrier and mixed and dispersed to produce a conductive paste for internal electrode formation (step 4).

[0050] Table 2 shows the ratio of the ionic radius of the A-site element under 6-coordinate to the ionic radius of the nickel under 6-coordinate to be included in the internal electrode, i.e., "ionic radius ratio (A-site element / metallic nickel)". Additionally, for sample 8, the ratio of the ionic radius of Ba under 6-coordinate (1.35 Å) shown in Table 1 to the ionic radius of Ni under 6-coordinate (0.69 Å) is shown.

[0051] 3. Fabrication of multilayer ceramic capacitors

[0052] A ceramic slurry containing the BaTiO3-based ceramic raw material powder prepared in step 1 above was prepared. Next, a ceramic green sheet was formed by applying a doctor blade to the ceramic slurry. Then, a conductive paste for forming internal electrodes, prepared in step 2 above, was screen-printed onto a given ceramic green sheet. Next, the multiple ceramic green sheets were stacked and then pressed together to obtain an untreated laminate. Next, the untreated laminate was sintered. Then, external electrodes were formed on the end faces of the sintered laminate to fabricate a multilayer ceramic capacitor as a sample.

[0053] 4. Evaluation

[0054] [Table 2]

[0055]

[0056] The internal electrodes and dielectric layer of the multilayer ceramic capacitor, located in the center of the stack in the height direction of the stack, are peeled off by electric field stripping.

[0057] Next, the area around the center of the exposed internal electrode (halfway in width and halfway in length) was observed using a microscope at 100x magnification. The resulting images were then analyzed to determine the proportion of the area occupied by the conductor film serving as the internal electrode in the exposed portion, which is shown as the "coverage rate" in Table 2. A coverage rate of 80% or higher was considered good and marked with "○" in the "Evaluation" column; a coverage rate below 80% was considered poor and marked with "×" in the "Evaluation" column.

[0058] 5. Research

[0059] The "Evaluation" for samples 1-3 and 5-7 in Table 2 is "○". In these samples 1-3 and 5-7, the internal electrode is an ABO3 oxide and contains any one of NiTiO3, MgTiO3, and MnTiO3. In addition, the internal electrode contains nickel as a conductive component.

[0060] Here, if we are concerned with the ionic radius, firstly, as shown in the "NiTiO3" item in Table 1, the ionic radius of nickel under 6-coordinate is 0.69 Å. On the other hand, as the ABO3 oxides contained in the internal electrodes of samples 1-3 and samples 5-7, the ionic radii of the elements at the A-site of NiTiO3, MgTiO3, and MnTiO3 under 6-coordinate are 0.69 Å, 0.72 Å, and 0.67 Å, ​​respectively, as shown in Table 1.

[0061] In samples 1-3 and 5-7, which were rated as “○”, the ratio of the ionic radius of the element at the A site in ABO3 under 6 coordination to the ionic radius of the metal element contained in the conductive metal particle under 6 coordination, i.e., the “ionic radius ratio”, is 0.97 or more and 1.04 or less.

[0062] In this way, in NiTiO3, MgTiO3, and MnTiO3, which are ABO3 oxides in samples 1-3 and 5-7, the ionic radius of the element at the A site of ABO3 under 6-coordinate is equal to or similar to the ionic radius of nickel under 6-coordinate, which is the conductive metal to be included in the internal electrode. Therefore, the energy difference between them and nickel in the internal electrode is 0 or small, so they will not be discharged from the internal electrode and remain there, thus playing a role and improving the heat resistance of the internal electrode. It is speculated that, as a result, the coverage becomes as high as 84% ​​or more in samples 1-3 and 5-7.

[0063] Furthermore, as with samples 5-7, the addition ratio of NiTiO3, MgTiO3, and MnTiO3 does not necessarily have to be 100%. As long as it is 10% or more, an improved coverage effect can be confirmed compared to the case where none of NiTiO3, MgTiO3, and MnTiO3 are present. In addition, in Experimental Example 1, it was noted that the coverage of samples 5-7, with an addition ratio of 10% of NiTiO3, MgTiO3, and MnTiO3, was equal to that of samples 1-3, with an addition ratio of 100%.

[0064] In contrast to these samples, in sample 4, which was rated "×", CuTiO3 was used as an ABO3 oxide. The ionic radius of Cu under 6-coordinate, as the A-site element in ABO3, is 0.73 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Cu under 6-coordinate to that of Nickel under 6-coordinate, i.e., the "ionic radius ratio", is 1.06. That is, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and the coverage becomes as low as 75%.

[0065] Furthermore, in sample 8, which was also rated "×", only BaTiO3, a common material, was added to the internal electrode. In this case, Ba, as the A-site element in the perovskite structure ABO3, is 12-coordinated. However, when dissolved in the A-site of the ilmenite structure, it is necessary to compare the ionic radius with that of Ba at the 6-coordinate position, which is 1.35 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Ba at the 6-coordinate position to that of Nickel at the 6-coordinate position, i.e., the "ionic radius ratio," is 1.96. Consequently, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and the coverage becomes as low as 74%.

[0066] It is speculated that in these samples 4 and 8, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and CuTiO3 and BaTiO3 will be ejected from the internal electrode portion, thus the heat resistance of the internal electrode is not improved and the coverage is reduced.

[0067] (Experimental Example 2) The main component of the ceramic that constitutes the dielectric layer: CaZrO3

[0068] 1. Preparation of CaZrO3-based ceramic raw materials constituting the dielectric layer

[0069] As starting materials, the powders of the main components CaCO3 and ZrO2 and the powders of the secondary components MnO, SiO2 and MgO were weighed and mixed in a ball mill for 72 hours. Then, the mixture was heat-treated at a maximum temperature of 1000℃ for 2 hours to obtain CaZrO3-based ceramic raw material powder.

[0070] 2. Preparation of conductive paste for internal electrode formation

[0071] The powder of “ABO3 oxide” shown in Table 3 below and the CaZrO3-based ceramic raw material powder used for the dielectric layer above are used as the ceramic powder contained in the conductive paste for forming the internal electrode.

[0072] The powders of these "ABO3 oxides" and CaZrO3 ceramic raw materials were weighed to achieve the "addition ratio" shown in Table 3. The conductive paste for forming internal electrodes was then prepared by following the same procedure as in Experimental Example 1 above.

[0073] Table 3, similar to Table 2, shows the "ionic radius ratio (A-site element / metallic nickel)". Additionally, for sample 18, the ratio of the ionic radius of Ca under 6-coordinate (1.00 Å) shown in Table 1 to the ionic radius of Ni under 6-coordinate (0.69 Å) is shown.

[0074] 3. Fabrication of multilayer ceramic capacitors

[0075] A ceramic slurry containing the CaZrO3-based ceramic raw material powder prepared in step 1 above was prepared. Next, a ceramic green sheet was formed by applying a scraper to the ceramic slurry. Subsequently, following the same procedures as in Experimental Example 1, a multilayer ceramic capacitor was fabricated as a sample.

[0076] 4. Evaluation

[0077] [Table 3]

[0078]

[0079] Following the same procedure as in Experiment Example 1, as shown in Table 3, the "coverage" was calculated and evaluated in the same way.

[0080] 5. Research

[0081] The "Evaluation" for samples 11-13 and 15-17 in Table 3 is "○". In these samples 11-13 and 15-17, the internal electrode is an ABO3 oxide and contains any one of NiTiO3, MgTiO3, and MnTiO3. In addition, the internal electrode contains nickel as a conductive component.

[0082] Here, if we are concerned with the ionic radius, firstly, as shown in the "NiTiO3" item in Table 1, the ionic radius of nickel under 6-coordination is 0.69 Å. On the other hand, as the ABO3 oxides contained in the internal electrodes of samples 11-13 and samples 15-17, the ionic radii of the elements at the A-site of NiTiO3, MgTiO3, and MnTiO3 under 6-coordination are 0.69 Å, 0.72 Å, and 0.67 Å, ​​respectively, as shown in Table 1.

[0083] In samples 11-13 and 15-17, which were rated as “○”, the ratio of the ionic radius of the element at the A site in ABO3 under 6 coordination to the ionic radius of the metal element contained in the conductive metal particle under 6 coordination, i.e., the “ionic radius ratio”, is 0.97 or more and 1.04 or less.

[0084] It is speculated that, as in NiTiO3, MgTiO3, and MnTiO3, which are ABO3 oxides in samples 11-13 and 15-17, the ionic radius of the A-site element in ABO3 under 6-coordinate is equal to or similar to the ionic radius of nickel under 6-coordinate, which is the conductive metal to be included in the internal electrode. Therefore, the energy difference between them and nickel in the internal electrode is 0 or smaller, so they will not be discharged from the internal electrode and remain there, thus playing a role in improving the heat resistance of the internal electrode. As a result, the coverage rate is as high as 81% or more in samples 11-13 and 15-17.

[0085] Furthermore, as with samples 15-17, the addition ratio of NiTiO3, MgTiO3, and MnTiO3 does not necessarily have to be 100%. As long as it is 10% or more, the effect of improved coverage can be confirmed compared with the case where any of NiTiO3, MgTiO3, and MnTiO3 is not included.

[0086] In contrast to these samples, in sample 14, which was rated "×", CuTiO3 was used as an ABO3 oxide. The ionic radius of Cu under 6-coordinate, as the A-site element in ABO3, is 0.73 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Cu under 6-coordinate to that of Nickel under 6-coordinate, i.e., the "ionic radius ratio", is 1.06. That is, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and the coverage becomes as low as 75%.

[0087] Furthermore, in sample 18, which was also rated "×", only CaZrO3, a common material, was added to the internal electrode. In this case, Ca, as the element at the A-site in the perovskite structure ABO3, is 12-coordinated. However, when dissolved at the A-site in the ilmenite structure, the ionic radius at the 6-coordinate, which is the coordination number at the A-site in the ilmenite structure, needs to be compared. The ionic radius of Ca at the 6-coordinate is 1.00 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Ca at the 6-coordinate to that of Nickel at the 6-coordinate, i.e., the "ionic radius ratio," is 1.45. Consequently, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and the coverage becomes as low as 72%.

[0088] It is speculated that in these samples 14 and 18, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and CuTiO3 and CaZrO3 will be ejected from the internal electrode portion, thus the heat resistance of the internal electrode is not improved and the coverage is reduced.

[0089] (Experimental Example 3) The main component of the ceramic that constitutes the dielectric layer: SrTiO3

[0090] 1. Preparation of SrTiO3-based ceramic raw materials constituting the dielectric layer

[0091] As starting materials, the powders of the main components SrCO3 and TiO2 and the powders of the secondary components MnO, SiO2 and MgO were weighed and mixed in a ball mill for 72 hours. Then, the mixture was heat-treated at a maximum temperature of 1000℃ for 2 hours to obtain SrTiO3 ceramic raw material powder.

[0092] 2. Preparation of conductive paste for internal electrode formation

[0093] The powder of “ABO3 oxide” shown in Table 4 below and the SrTiO3-based ceramic raw material powder used for the dielectric layer above are used as the ceramic powder contained in the conductive paste for forming the internal electrode.

[0094] The powders of these "ABO3 oxides" and SrTiO3 ceramic raw materials were weighed to achieve the "addition ratio" shown in Table 4. The conductive paste for forming internal electrodes was prepared by following the same procedure as in Experimental Example 1 above.

[0095] Table 4, similar to Table 2, shows the "ionic radius ratio (A-site element / metallic nickel)". Additionally, for sample 28, the ratio of the ionic radius of Sr under 6-coordinate (1.18 Å) shown in Table 1 to the ionic radius of Ni under 6-coordinate (0.69 Å) is shown.

[0096] 3. Fabrication of multilayer ceramic capacitors

[0097] A ceramic slurry containing the SrTiO3-based ceramic raw material powder prepared in step 1 above was prepared. Next, a ceramic green sheet was formed by applying a scraper to the ceramic slurry. Subsequently, following the same procedures as in Experimental Example 1, a multilayer ceramic capacitor was fabricated as a sample.

[0098] 4. Evaluation

[0099] [Table 4]

[0100]

[0101] Following the same procedure as in Experiment Example 1, as shown in Table 4, the “coverage” was calculated and evaluated in the same way.

[0102] 5. Research

[0103] The "Evaluation" for samples 21-23 and 25-27 in Table 4 is "○". In these samples 21-23 and 25-27, the internal electrode is an ABO3 oxide and contains any one of NiTiO3, MgTiO3, and MnTiO3. In addition, the internal electrode contains nickel as a conductive component.

[0104] Here, if we are concerned with the ionic radius, firstly, as shown in the "NiTiO3" item in Table 1, the ionic radius of nickel under 6-coordinate is 0.69 Å. On the other hand, as the ABO3 oxides contained in the internal electrodes of samples 21-23 and samples 25-27, the ionic radii of the elements at the A-site of NiTiO3, MgTiO3, and MnTiO3 under 6-coordinate are 0.69 Å, 0.72 Å, and 0.67 Å, ​​respectively, as shown in Table 1.

[0105] In samples 21-23 and 25-27, which were rated as “○”, the ratio of the ionic radius of the element at the A site in ABO3 under 6 coordination to the ionic radius of the metal element contained in the conductive metal particle under 6 coordination, i.e., the “ionic radius ratio”, is 0.97 or more and 1.04 or less.

[0106] It is speculated that, as in NiTiO3, MgTiO3, and MnTiO3, which are ABO3 oxides in samples 21-23 and 25-27, the ionic radius of the A-site element in ABO3 under 6-coordinate is equal to or similar to the ionic radius of nickel under 6-coordinate, which is the conductive metal to be included in the internal electrode. Therefore, the energy difference between them and nickel in the internal electrode is 0 or smaller, so they will not be discharged from the internal electrode and remain there, thus playing a role and improving the heat resistance of the internal electrode. As a result, the coverage rate is as high as 80% or more in samples 21-23 and 25-27.

[0107] Furthermore, as with samples 25–27, the addition ratio of NiTiO3, MgTiO3, and MnTiO3 does not necessarily have to be 100%. As long as it is 10% or more, the effect of improved coverage can be confirmed compared with the case where any of NiTiO3, MgTiO3, and MnTiO3 is not included.

[0108] In contrast to these samples, in sample 24, which was rated "×", CuTiO3 was used as an ABO3 oxide. The ionic radius of Cu under 6-coordinate, as the A-site element in ABO3, is 0.73 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Cu under 6-coordinate to that of Nickel under 6-coordinate, i.e., the "ionic radius ratio", is 1.06. That is, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and the coverage becomes as low as 72%.

[0109] Furthermore, in sample 28, which was also rated "×", only SrTiO3, a common material, was added to the internal electrode. In this case, Sr, as the A-site element in the perovskite structure ABO3, is 12-coordinated. However, when dissolved in the A-site of the ilmenite structure, it is necessary to compare the ionic radius with that of 6-coordinate, which is the coordination number of the A-site in the ilmenite structure. The ionic radius of Sr under 6-coordinate is 1.18 Å, as shown in Table 1. Therefore, the ratio of the ionic radius of Sr under 6-coordinate to that of nickel under 6-coordinate, i.e., the "ionic radius ratio," is 1.71. Consequently, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and the coverage becomes as low as 70%.

[0110] It is speculated that in these samples 24 and 28, the "ionic radius ratio" falls outside the range of 0.97 to 1.04, and CuTiO3 and SrTiO3 are ejected from the internal electrode portion, thus the heat resistance of the internal electrode is not improved and the coverage is reduced.

[0111] In Experimental Examples 1 to 3 described above, nickel powder was used as the conductive metal powder contained in the conductive paste for forming the internal electrodes. In most commercially available multilayer ceramic capacitors, nickel is used as the conductive component of the internal electrodes; therefore, using nickel powder as the conductive metal powder contained in the conductive paste for forming the internal electrodes is advantageous in reducing design changes.

[0112] However, conductive metal powders other than nickel powder can also be used as conductive metal powders. Therefore, the powder comprising at least a portion of the ceramic powder included in the conductive paste, which is an ABO3-type oxide with a specific ionic radius, can also be a powder other than at least one selected from NiTiO3, MgTiO3, and MnTiO3. That is, regarding the ABO3-type oxide with a specific ionic radius, any ABO3-type oxide can be used as long as the ratio of the ionic radius of the element at the A site in ABO3 under 6-coordinate to the ionic radius of the metal element included in the conductive metal powder of the conductive paste is 0.97 or more and 1.04 or less.

[0113] Explanation of reference numerals in the attached figures

[0114] 1: Multilayer ceramic capacitor;

[0115] 2: Layered body;

[0116] 3: Dielectric layer;

[0117] 4, 5: Internal electrodes;

[0118] 6, 7: External electrodes.

Claims

1. A conductive paste, comprising conductive metal powder, ceramic powder, organic solvent, and organic binder, for forming the internal electrodes of a laminated ceramic capacitor, wherein... At least a portion of the ceramic powder is a powder containing an ABO3-type oxide with a specific ionic radius, wherein in the ABO3-type oxide with the specific ionic radius, the ratio of the ionic radius of the element at the A-site of the ABO3 element under 6-coordinate to the ionic radius of the metal element contained in the conductive metal powder under 6-coordinate is 0.97 or more and 1.04 or less. The oxides of the ABO3 type with the specific ionic radius have an ilmenite crystal structure. The ABO3 type oxide with the specific ionic radius is selected from at least one of NiTiO3 and MnTiO3.

2. The conductive paste according to claim 1, wherein, The conductive metal powder contains nickel.

3. The conductive paste according to claim 1 or 2, wherein, More than 10% by volume of the ceramic powder is a powder containing an ABO3-type oxide with the specific ionic radius, and the remainder of the ceramic powder is a powder with at least one of BaTiO3, SrTiO3 and CaZrO3 as the main component.

Citation Information

Patent Citations

  • Conductive paste and production method of the same

    JP2016031807A

  • Nickel composite conductor for forming electrode and laminated ceramic capacitor

    JP2000232032A